PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2018 - Aziatul, Reny; Munandar, Aris; Veronica, Meilin; Meihazura, Yulita (Jurnal Keuangan dan Bisnis, 2020)
This study aims to analyze the effect of account receivables turnover and inventory turnover on profitability measured by Return On Investment (ROI). The population of this research was the Retail Trading Sub Sector Listed on the Indonesia Stock Exchange (IDX). Data in the form of secondary data were collected using literature studies and documentation techniques. Data were analyzed using panel data regression analysis and tested with T-Test, F-Test, and Determination Coefficient Test (R2) processed with Eviews version 9. The test results concluded that the account receivables turnover and inventory turnover simultaneously have a significant effect on profitability. Partially, account receivables turnover has no significant effect on profitability, whereas inventory turnover has a significant effect on profitability.